The problem of choice in the tragedy by Yelysey Karpenko “Momot Nir” - Атаманчук, Вікторія Петрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article is devoted to the elucidation of the genre features in literary work by Yelysey Karpenko “Momot Nir”. The article defines the correlation between genre and content parameters of literary work. Particular attention is paid to determining the specificity of artistic expression the problem of choice made by characters and the consequences of their choice. The originality of the conflict formation and the development of action in the playwright’s play is revealed. The work depicts the duality of the image: personal tragedies, which were the result of misconceptions and actions of characters in combination with the coincidence of various unfavorable factors, are fully unfolding in the final part – just when the greatest progress is achieved by the people’s movement for national liberation. The images of the characters of the literary work are studied through comparison of their ideas, emotions, actions. The symmetric interdependence of the characters’ actions of the tragedy is determined. Elysey Karpenko, depicting Momot Nir as the central figure in the tragedy, has determined the way of conflict unfolding in the personal and national plane. Momot does not defend his own personal sovereignty and spiritual values; the decision is not taken independently. Paradoxically, it seems to him that he does all for the sake of a national idea. The playwright emphasized the interdependence of actions that influence the process of self-determination of heroes and the formation of their moral values.